Sistem Penyiraman Otomatis Berbasis IoT dengan Logika Fuzzy Sugeno untuk Pengendalian Kelembaban Tanah di Greenhouse - Saragih, Khoirul Azmi; Kurniawan, Rakhmat (Jurnal Algoritma, 2025)
Modern agriculture demands an efficient and adaptive irrigation system, especially in spinach (Amaranthus sp.) cultivation which requires optimal soil moisture for maximum growth. Manual watering is often inefficient and prone to irregularities. This study aims to design and implement an automatic watering system based on the Internet of Things (IoT) with the Fuzzy Sugeno method in a greenhouse. This system uses an ESP8266 microcontroller integrated with a soil moisture sensor, DHT11 temperature sensor, RTC module, and relay to control the water pump. In addition, an Android application was developed using MIT App Inventor connected to Firebase, allowing real-time monitoring and control of the system in three modes: manual, scheduling, and fuzzy-based automatic. The Fuzzy Sugeno method is used to determine the duration of watering adaptively based on temperature and soil moisture parameters. The test results show that this system is able to respond to changes in soil moisture with 90% accuracy and increase water use efficiency by 25% compared to the manual method. The implementation of this system is expected to increase water use efficiency and support automation in precision agriculture.